Probing the possible trigger mechanisms of an equatorial plasma bubble event based on multistation optical data - Taori, A.; Parihar, Navin; Ghodpage, R.N.; Dashora, N.; Sripathi, S.; Kherani, E.A.; Patil, P.T. (My University, 2015)
We analyze an equatorial plasma bubble (EPB) event observed in optical 630 nm image data simultaneously from Gadanki (13.5°N, 79.2°E), Kolhapur (16.8°N, 74.2°E), India. The total electron content data from Gadanki together with the ionosonde data from an equatorial Indian station, Tirunelveli (8.7°N, 77.8°E) confirmed the association of observed EPB event with equatorial spread F (ESF). The optical 630 nm images from a farther low-latitude Indian station Ranchi (23.3°N, 85.3°E) show clear signatures of tilted east-west wave structures propagating toward equator. Further, the upward wave energy noted in mesospheric airglow data was found to be negligible. These data suggest that possibly the off-equatorial tilted east-west structures triggered the observed EPB/ESF event.
Keywords: Equatorial Plasma bubble; EPB; Optical data; Optical data; Mesospheric waves; Optical 630nm image data; Kolhapur; Ranchi; Tirunelveli; Gadanki